A Framework for Reducing the Cost of the Firewall - Alwajeeh, Mohammed; Noman Alassali, Saleh; Ali Alahmadi, Yasser (International Journal of Computer Sciences and Engineering, 2023)
Today, the world has become like a small village, and the success of any institution has become closely related to communication with the outside world through the Internet. As each institution needs to exchange information from one place to another that exposes sensitive information to danger and spread. Such institutions require the existence of mechanisms to protect this information. The firewall plays an important role in protecting information from unauthorized access. However, the available firewalls are not suitable for all institutions due to their high cost. This paper proposes a micro-firewall for reducing the cost of firewall by avoiding the additional services while maintaining the security, and thus the proposed micro-firewall will suitable the small and medium institutions. The proposed micro-firewall uses two computers, one of them is connected with the internet and the other is connected with the local network, the communication between the two computers is done by using the server and client protocols. The role of the computer connected with the internet is to receive the request from the external user who want access the internal network and verify the identity of the user if he/she is an authorized user or not. If yes it sends the request to the computer connected with the internal network, unless the request is rejected. The role of internal computer is similar to external computer but for internal user. The proposed micro-firewall was compared with other firewalls in terms of the cost reduction. The results showed that the cost of proposed micro-firewall has reduced compared with the cost of the other firewalls.